Psychometric validation of the Epworth Sleepiness Scale for Children and Adolescents (ESS-CHAD) in Slovenia - Mlakar, Ajda (Zdravstveno varstvo, 2026)
Introduction This study aimed to develop a suitable instrument for assessing excessive daytime sleepiness (EDS) in Slovenian children and adolescents by translating the ESS-CHAD and psychometrically validating its Slovenian version (ESS-CHAD-SI). Methods The ESS-CHAD was translated and back-translated according to established cross-cultural adaptation guidelines, and content validity was assessed by eleven experts from relevant clinical and research disciplines. A nationwide sample of 3,314 adolescents (?52% females), with an overall mean age of 15.4±1.7 years, completed the questionnaire. Reliability was evaluated using Cronbach’s ? and Guttman’s ?2, and construct validity was examined using exploratory and confirmatory factor analyses. Results All items met the predefined thresholds for content relevance, while clarity indices were acceptable for the majority of items. Factor analyses indicated that a two-factor model provided a better fit to the data than the original unidimensional structure, distinguishing between passive sleepiness and more clinically concerning manifestations of sleepiness. The ESS-CHAD-SI demonstrated adequate internal consistency. Conclusions The ESS-CHAD-SI is a reliable, valid, and culturally adapted instrument for assessing excessive daytime sleepiness in Slovenian adolescents. The identified two-factor structure enhances its clinical and public health relevance by enabling differentiation between sleepiness related to modifiable sleep behaviours and potentially pathological somnolence. The scale is suitable for use in school-based screening, clinical practice, and epidemiological research.
Keywords: adolescents; čezmerna dnevna zaspanost; excessive daytime sleepiness; mladostniki; questionnaires; Slovenia; Slovenija; validacija; validation; vprašalniki